Sexual violence experienced by male and female Chinese college students in Guangzhou. (7th January 2014) - Wang, Chang; Dong, Xiaomei; Yang, Jingzhen; Ramirez, Marizen; Chi, Guibo; Peek-Asa, Corinne; Wang, Shengyong
Abstract : Objectives: Sexual violence research in China is in its early stages. This study described the sexual violence experience of college students in Guangzhou, China, and examined the individual and family factors associated with increased sexual perpetration and victimisation. Methods: A cross-sectional survey of 2200 college students from three universities in Guangzhou, China, was conducted in 2010. Data on sexual perpetration and/or victimisation experienced during the past 12 months were collected. Multinomial logistic regression was used to assess the individual and family factors associated with odds of sexual assault perpetration, victimisation, or both. Results: Over a quarter (25.4%) of students experienced at least one form of sexual violence during the past 12 months, either as a perpetrator or as a victim, and nearly 10% of students experienced both perpetration and victimisation. The number of students who identified themselves as being solely a victim was almost three times lower than being a perpetrator only (n=87 vs n=246). Engaging in risky behaviours was associated with increased odds of being a perpetrator and being both a perpetrator and a victim. Prior mistreatment by teachers or bullying by others was linked to increased risk of both perpetration and victimisation. Male students who had indulgent parents (responsive but not demanding) were at increased risk of perpetration compared with those students with authoritative parents (responsive and demanding). Conclusions: The findings add to empirical data on sexual violence in college students and reinforce the urgent need for implementation of successful sexual violence prevention programmes in China.